Influence of Transformational Leadership on Novelty of Product Ideas: Validation of Theoretical Model - Ahmetasevic, Jasminka; Obralic, Merdzana (European Scientific Journal, ESJ, 2018)
This study investigates the relationship between transformational leadership and novelty of product ideas. Conceptual approach based on the theory has been applied to provide better understanding of the relationship between transformational leadership and two knowledge creation modes (internalization, externalization). Mediating roles of internalization and externalization in a relationship between transformational leadership and novelty of product ideas will be investigated. After conducting a systematic literature review, theoretical model will be proposed and validated using regression analysis. Main software packages used in this study are Microsoft Word and Statistical Package for Social Sciences. This is one of the first studies to explore the link between transformational leadership and novelty of product ideas. It, however, has two important knowledge creation modes, internalization and externalization as mediators. The main finding of this paper is the validation of theoretical model which mostly confirmed assumptions based on previous literature. Regression tests indicated confirmation of five hypotheses, while mediation tests indicated partial mediation of Internalization and Externalization. It is recommended that future research should conduct validation of the model using other methodologies and different samples, or same samples in different time periods, to provide stronger empirical evidence for the confirmation of tested hypotheses.